2010
DOI: 10.1016/j.fct.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus section Flavi and aflatoxins in Algerian wheat and derived products

Abstract: Wheat and its derivatives are a very important staple food for North African populations. The aim of this study was to analyze populations of Aspergillus section Flavi from local wheat based on aflatoxins (AFs), cyclopiazonic acid (CPA) and sclerotia production, and also to evaluate AFs-contaminated wheat collected from two different climatic regions in Algeria. A total of 108 samples of wheat were collected during the following phases: pre-harvest, storage in silos and after processing. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 32 publications
8
72
1
Order By: Relevance
“…The molecular identification of the obtained monosporic isolates revealed that they were all A. flavus (Table 1). The occurrence of A. flavus and not of A. parasiticus was also reported in wheat grown and consumed in Lebanon (Joubrane et al, 2011) and Algeria (Riba et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The molecular identification of the obtained monosporic isolates revealed that they were all A. flavus (Table 1). The occurrence of A. flavus and not of A. parasiticus was also reported in wheat grown and consumed in Lebanon (Joubrane et al, 2011) and Algeria (Riba et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The most common genera are Aspergillus, Penicillium, Fusarium, and Alternaria isolated from wheat grain in Saudi Arabia (Al-Hazmi, 2010;Gashgari et al, 2010). The contamination of cereal grains by fungi is a worldwide problem, where there are several reports documenting the presence of these fungi in samples from the United States (Cleveland et al, 2003), Argentina (Roige et al, 2009), Spain (Sardiñas et al, 2011), and Algeria (Riba et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While 12 strains from peanut and 5 from wheat were high producers. Several studies reported the aflatoxigenic potential of different A. flavus strains collected from various seeds and grains all over the world (Riba et al, 2010, Ezekiel et al, 2012, Kana et al, 2013and Fakruddin et al, 2015.…”
Section: Aflatoxin Productionmentioning
confidence: 99%